2020
DOI: 10.1007/s00259-019-04669-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of tau deposition are associated with amyloid, ApoE, sex, and cognitive decline in older adults

Abstract: Purpose The abnormal deposition of tau begins before the onset of clinical symptoms and seems to target specific brain networks. The aim of this study is to identify the spatial patterns of tau deposition in cognitively normal older adults and assess whether they are related to amyloid-β (Aβ), APOE, sex, and longitudinal cognitive decline. Methods We included 114 older adults with cross-sectional flortaucipir (FTP) and Pittsburgh Compound-B PET in addition to longitudinal cognitive testing. A voxel-wise indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 59 publications
5
33
1
Order By: Relevance
“…Some of the issues with development likely arise from the necessity of tau tracers to penetrate cell membranes, since misfolded tau forms intracellular inclusions, and the numerous isoforms of misfolded tau that are often disease specific. Nevertheless, PET studies confirm previous reports of tau as a better predictor of cognitive decline and cell death in AD compared to amyloid ( Cho et al, 2016 ; Kotzbauer et al, 2017 ; Gordon et al, 2018 ; Pereira et al, 2020 ). Newer tracers are being developed, and those such as 18F-RO-948 demonstrate an inverse relationship with cortical thickness ( Spotorno et al, 2020 ), which is in agreement with older tracers ( Ossenkoppele et al, 2019 ).…”
Section: Human Studiessupporting
confidence: 88%
“…Some of the issues with development likely arise from the necessity of tau tracers to penetrate cell membranes, since misfolded tau forms intracellular inclusions, and the numerous isoforms of misfolded tau that are often disease specific. Nevertheless, PET studies confirm previous reports of tau as a better predictor of cognitive decline and cell death in AD compared to amyloid ( Cho et al, 2016 ; Kotzbauer et al, 2017 ; Gordon et al, 2018 ; Pereira et al, 2020 ). Newer tracers are being developed, and those such as 18F-RO-948 demonstrate an inverse relationship with cortical thickness ( Spotorno et al, 2020 ), which is in agreement with older tracers ( Ossenkoppele et al, 2019 ).…”
Section: Human Studiessupporting
confidence: 88%
“…One study in two independent cohorts of cognitively normal subjects found that in the presence of high amyloid burden, women had higher entorhinal tau load than man [13]. This observation was confirmed in a study showing higher tau retention in temporo-parietal and frontal areas in women [95]. Another study suggested that men have higher uptake mainly in the frontal and parietal white matter and thalamus than women [128], although this was hypothesized to be largely driven by non-specific binding.…”
Section: Phase 2 Secondary Aimmentioning
confidence: 94%
“…Furthermore, a study in healthy controls (41.2% Aβ+) found higher tau SUVrs in the parahippocampal gyrus in ɛ3ɛ3 carriers compared to ɛ2ɛ3 carriers, after adjusting for amyloid. This potentially shows the protective effect of the ɛ2 allele, although this must be interpreted with caution since the number of ɛ2ɛ3 carriers was limited (n = 11) [95].…”
Section: Phase 2 Secondary Aimmentioning
confidence: 97%
See 1 more Smart Citation
“…The aggregations of tau proteins are found in temporal, ventral, lateral, and primary cortical areas of brain. Notably, the enhanced levels of tau proteins in temporal and frontal areas have most significant impacts on the decline in the memory and brain functions (Pereira, Harrison, La Joie, Baker, & Jagust, 2020). Interestingly, accumulation of tau proteins produces a signal of “eat‐me” on living neurons.…”
Section: Tau Protein and Pathological Eventsmentioning
confidence: 99%